IMPLEMENTATION OF IoT FOR NUTRITION MONITORING AND CONTROL IN OPTIMIZING HYDROPONIC CROP PRODUCTION IN GREENHOUSE - Rouhillah, Rouhillah; Susilawati, Feri; Ramadhan, Rizki (LPPM Universitas Flores, 2025)
This community service program aims to enhance the efficiency and productivity of hydroponic kale cultivation by leveraging the Internet of Things (IoT) technology. The activity partners are greenhouse managers in Beurawe Village, Kuta Alam District. The primary challenges faced by partners include limited monitoring tools for pH and EC levels of nutrient solutions, minimal technical expertise, and a lack of knowledge about plant nutrition and digital marketing. The solutions offered include training in the installation and use of an IoT System implemented using pH and TDS sensors connected to a Wemos D1 Mini microcontroller and displaying data in real-time through a digital dashboard, the preparation of a kale nutrient module, the implementation of a data-based automation system, and digital marketing training. This program is expected to increase the efficiency and productivity of hydroponics, especially in nutrient monitoring and control. Increasing the efficiency and productivity of hydroponics, especially in nutrient monitoring and control and being able to increase water use efficiency by up to 15%, reduce nutrient use by 20%, and increase plant productivity by 20%. This activity involves lecturers and students and supports MBKM policies and the development of sustainable technology-based precision agriculture in the community.